Using English as a second language online: digital interactions and their implications for language learning and teaching - Moffat, Andrew D. (2020)
The growth of internet connectivity has made online communication ubiquitous and unremarkable. For speakers of English as a second language (L2), this computer-mediated communication (CMC) may present opportunities for engagement with the language which may be otherwise lacking in their offline context. Such exposure to the language in naturalistic interaction would undoubtedly have implications for their relationship to the language and any formal instruction of it in which they might be involved. For language teaching not to take such implications into account is to risk a failure to make classroom learning relevant to the lives and needs of learners, and to miss the opportunity to exploit the learning benefits of this communicative use of the target language.